2011
DOI: 10.1007/s10658-010-9722-x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of different plant species and tomato cultivars to two isolates of Pepino mosaic virus

Abstract: As Pepino mosaic virus has become a pathogen of major importance in worldwide tomato production, information is needed on possible differences between the sensitivity of cultivars towards infection. Furthermore, it is important what hosts other than Solanaceae may be virus reservoirs and are, therefore, threats for tomato cultivation. Two PepMV isolates (PepMV-Sav, E397, a European tomato isolate and PV-0554, a Peruvian pepino isolate) differing in their origin and virulence were used for several experiments t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
8
1
Order By: Relevance
“…The plant pathogen Pepino mosaic virus (PepMV), a highly infectious potex virus, is one of the major global diseases of greenhouse tomato crops [1][3]. Different PepMV isolates can cause a wide range of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The plant pathogen Pepino mosaic virus (PepMV), a highly infectious potex virus, is one of the major global diseases of greenhouse tomato crops [1][3]. Different PepMV isolates can cause a wide range of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…benthamiana does not differentiate the three isolates as clearly as N. occidentlais 37B and N. rustica, but may be a useful propagation host. Fakhro et al (2011) recorded clear symptoms and the highest virus concentration in N. benthamiana when comparing seven Nicotiana species. Other papers also report systemic symptoms in N. benthamiana (Martin and Mousserion 2002;Salomone and Roggero 2002;Van der Vlugt et al 2002;Pospieszny et al 2008;Gómez et al 2009;Hasiów-Jaroszewska et al 2010a).…”
Section: Tomato (S Lycoperiscum)mentioning
confidence: 94%
“…Beate inoculated with the isolate TomA2001-1 (a Ch2 genotype isolate, Van der Vlugt unpublished) showed that a systemic infection can occur in combination with a sensitive cultivar and that the virus can be transmitted through the tubers. Jones et al (1980) also recorded symptomless infection in four potato cultivars, Martin and Mousserion (2002) recorded infection and symptom development in four out of seven inoculated potato cultivars, and Fakhro et al (2011) recorded symptomless infection with an EU-tom strain isolate in a single cultivar.…”
Section: Potato (S Tuberosum)mentioning
confidence: 95%
See 2 more Smart Citations